KONSEPSI EKONOMI ISLAM UNTUK PEMBANGUNAN EKONOMI NEGARA - Ikhwan, Afiful (LIPI, 2014)
Based on this conception of the role of the state is very important for the application of Islamic economics. Without the state, the Islamic economy will not be able to contribute to solving the economic problem and the establishment of a fair economic structure. Similarly, without taking Islamkan Islamic countries can not also be the axis of economic policy and development.